MHC Diversity Across Time and Space - Maria Cortazar‐Chinarro; Kayla C. King; Mette Lillie (Ecology and Evolution, 2025)
ABSTRACT Most natural populations are genetically diverse. Understanding how diversity is maintained and distributed across time and space can provide insights into the potential for evolution and extinction of populations. Immunogenetic diversity aids individuals and populations in resisting infectious disease, with many studies linking resistance to genes encoding adaptive immune responses, such as the major histocompatibility complex (MHC) genes. The MHC is particularly important for advancing our understanding of local adaptive processes and host–parasite interactions. Here, we review the emerging work and theory exploring the geographic and temporal patterns of MHC diversity in the wild and how they are shaped by selective and demographic processes. We discuss patterns of variation along latitudinal and altitudinal gradients and place this in the context of Latitude Diversity Gradient and Central Marginal Theories. We emphasize how MHC diversity is often lower at the edges of species distributions, particularly in high‐latitude and high‐altitude regions. We also discuss MHC diversity in natural populations facing climate change. As climate change accelerates and emerging parasites spread, reduced immunogenetic diversity could severely threaten wildlife populations, compromising their resilience and long‐term survival. We propose that including immunogenetic diversity into a larger database of environmental and parasite data would allow biologists to test hypotheses regarding host–parasite coevolution and develop effective measures for conservation.